Faktor-Faktor yang Mempengaruhi Harga Saham pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Nurhamidah Nurhamidah; Wirmie Eka Putra (AKUNTANSI 45, 2026)
This study aims to examine the factors influencing stock prices in banking companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research focuses on the effect of profitability ratio, solvency ratio, firm size, and activity ratio on stock prices. This study employs a quantitative research method using secondary data obtained from the annual financial statements of banking companies. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The findings indicate that partially, profitability ratio, solvency ratio, and firm size have a positive and significant effect on stock prices, while the activity ratio does not have a significant effect on stock prices. Simultaneously, all independent variables significantly influence stock prices, with a coefficient of determination (R²) of 0.998, indicating that 99.8% of the variation in stock prices can be explained by the variables used in this study. These results imply that the financial performance and characteristics of banking companies are important considerations for investors in making investment decisions in the capital market, particularly in the banking sector.